Malignant fibrous histiocytoma in a patient presenting with urinary system symptoms - Resorlu,Mustafa (2017)
Summary Malignant fibrous histiocytoma is a rare tumor. It is most commonly seen in individuals between the fifth and seventh decades of life, in extremities, and less frequently in the retroperitoneum. Although its etiology is not clearly known, radiotherapy, chemical agents, previous history of surgery, trauma and fracture, and Hodgkin lymphoma have been blamed. Leiomyosarcoma, liposarcoma and rhabdomyosarcoma should be taken into account in differential diagnosis. It is seen on computed tomography as a mass lesion with irregular borders and density similar to that of the surrounding muscle tissue. Necrotic and hemorrhagic components in the mass are characterized as heterogeneous low density areas. Fluid-fluid levels can be detected by computed tomography and magnetic resonance imaging.